Scientific Paradigm Towards World-Class University: Comparative Study on UIN Sunan Kalijaga Yogyakarta and UIN Maulana Malik Ibrahim Malang - Sekar Ayu Aryani; Sunarsih Sunarsih; Kurnia Rahman Abadi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
The State Islamic University (UIN) Maulana Malik Ibrahim Malang’s scientific paradigm of Integration depicted in “the tree of knowledge”, describes the non-dichotomic scientific structure, placing the Qur’an and the Hadith as the source. With the support of a set of observations, experiments, and other scientific research procedures, the values of the Qur’an and Hadith are being articulated into scientific theories and concepts to be applied in the implementation of “Tri Dharma Perguruan Tinggi” (Three Pillars of Tertiary Education). While State Islamic University (UIN) Sunan Kalijaga has a scientific paradigm of the “Integration-Interconnection” which originated from the critical-philosophical study of the history of science, to be implemented in contemporary context. The formulation of the scientific paradigm is conceptualized in “the cobwebs of sciences” and applied in the academic policies and management in UIN Sunan Kalijaga. The scientific paradigm of UIN Maulana Malik Ibrahim Malang and UIN Sunan Kalijaga shares similarities in terms of non-dichotomous attitude towards science, either from the Islamic tradition, Western paradigm or other scientific traditions. The difference of both lies in the emphasis of paradigm formulation. While UIN Sunan Kalijaga emphasizes some aspects of integration, UIN Maliki puts the openness attitude of Islam to all kinds of science as the point of accentuation. With regard to the application of the scientific paradigm of UIN Maulana Malik Ibrahim Malang and UIN Sunan Kalijaga for the development of a world-class university, according to researchers, both are potential subject to the development toward world-class university. It is due to the openness nature both have for the development of sciences and to the higher possibility of public usage of both for community development.[Paradigma keilmuan Integrasi UIN Maulana Malik Ibrahim Malang yang digambarkan dalam bentuk Pohon Ilmu menggambarkan struktur keilmuan non dikhotomis dimana Alqur ’an dan Hadis sebagai sumbernya. Dengan bantuan observasi dan eksperimen serta serangkaian prosedur penelitian ilmiah lainnya, nilai-nilai Alqur ’an dan Hadis dikembangkan menjadi teori dan konsep ilmu pengetahuan untuk kemudian diterapkan dalam dalam pelaksanaan Tri Darma Perguruan Tinggi. Sementara UIN Sunan Kalijaga memiliki paradigma keilmuan “Integrasi-Interkoneksi” yang berangkat dari telaah kritis-filosofis terhadap sejarah ilmu kemudian didialektikakan dengan konteks kontemporer. Formulasi dari paradigma keilmuan tersebut dikonsepkan dengan “jaring laba-laba keilmuan” dan diaplikasikan dalam kebijakan akademik dan manajemen di UIN Sunan Kalijaga. Kedua, Paradigma keilmuan UIN Maulana Malik Ibrahim Malang dan UIN Sunan Kalijaga memiliki persamaan pada aspek sikap non-dikotomis terhadap ilmu pengetahuan baik yang bersumber dari tradisi Islam maupun dari Barat atau tradisi keilmuan lain.Perbedaan paradigma keilmuan UIN Maulana Malik Ibrahim Malang dan UIN Sunan Kalijaga terletak pada titik tekan formulasi paradigmanya. Jika UIN Sunan Kalijaga menekankan aspek integrasi, UIN Maliki Malang lebih pada sifat keterbukaan Islam terhadap segala jenis keilmuan. Ketiga, berkaitan dengan penerapan paradigma keilmuan UIN Maulana Malik Ibrahim Malang dan UIN Sunan Kalijaga bagi pengembangan world class university, menurut hemat peneliti kedua-duanya potensial untuk dikembangkan pada World Class University. Argumennya, karena keduanya punya sifat terbuka untuk pengembangan berbagai keilmuan dan dapat digunakan bagi pengembangan masyarakat secara lebih luas.]